Brain wave activity differences in task complexity and perspective during imagery - Vangen, R.; Post, P.; Simpson, D.; Cremades, G. (Journal of Imagery Research in Sport and Physical Activity, 2017)
The present study investigated how task complexity and imagery perspective affected brain wave activity during imagery using electroencephalography (EEG) measures. EEG recordings were collected from 21 collegiate soccer players (male n = 14, female n = 7; M age = 20.71 years, SD = 1.55) visualizing from two perspectives (internal and external) on two motor tasks (simple and complex). Results reveal no differences in alpha brainwave activity during imagery when adopting different imagery perspectives (internal and external) or when imagining a complex or simple task. Results indicate that the left hemisphere was processing more information during imagery of the simple task, as measured by greater alpha brain wave activity in the upper values (11-13 Hz) in the right hemisphere as compared to the left. Findings indicate that the main area of the brain where this activity is different is the temporal lobe (lower and upper alpha levels), which is associated with the processing of auditory information, visual recognition, comprehension and production of language (Corr, 2006). Results imply that guided imagery scripts may interfere with athletes` imagery experiences as they appear to be devoting greater cognitive resources to processing audio information.